Evaluation of mid trimester abortion (13-20 weeks) using newer regimen of mifepristone with misoprostol versus misoprostol alone - Singh, Vinita; Sethia, Ritika; Murmu, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Termination of pregnancy in second trimester continues to be a challenge in developing countries especially in rural areas. There is an exponential rise in complications of abortion along with advancing gestational age. The search is on for an ideal method of abortion which is reliable, safe and cheap. This study was conducted in Tata main hospital, Jamshedpur from 15th November 2012 to 14th November 2014, with the aim of finding an effective method to induce second trimester abortion within reasonable time with fewer complications. Methods: A total of 80 patients were studied to compare combination of mifepristone and misoprostol, with single drug misoprostol alone for second trimester abortion. The induction abortion interval (IAI), success rate and side effects were compared between the two groups. . Results: There was a significant difference in the IAI in both the groups. The mean IAI was 196.28 minutes in study group whereas in control group IAI was 318.92 minutes. The success rate (complete abortion) was 97.5% in study group and 92.5% in control group, but this was not statistically significant. More side effects were observed in the control group. Conclusions: Mifepristone followed by misoprostol was more effective than misoprostol alone as it had a shorter IAI and fewer side effects.